The Effect of Project Based Learning Assisted with Flashcards towards Students’ Learning Outcomes in Learning Pencak Silat - I Gede Suwiwa; I Ketut Budaya Astra; I Ketut Yoda; I Made Satyawan (CV Rezki Media, 2023)
Background: Motion-based learning, especially Pencak Silat material taught at the Senior High School level always presents challenges for Physical Education (PE) Teachers. Objectives: This study aimed to investigate the effect of project-based learning assisted with flashcards on students’ learning outcomes in learning Pencak Silat. Methods: Quasi-experimental was used as a research design by conducting pretest and posttest. There were 312 eleventh-grade students in this study, which was conducted at Senior High School of Laboratorium Universitas Pendidikan Ganesha (Undiksha) and Senior High School 1 Sukasada. A simple random sampling technique was performed to select the sample of this study. One hundred twenty students were chosen as a research sample and divided into experimental and control groups. The data were collected by conducting pre-tests and post-tests. The instrument used in this study was the basic attitudes test of Pencak Silat. The collected data were analyzed quantitatively through inferential statistics (independent sample t-test) with the assistance of SPSS 22. Results: The results showed a significant difference between the post-test gained by the experimental group treated by project-based learning assisted with flashcards and the control group treated by conventional education. Sig proved it. (2-tailed) the post-test data was 0.01, indicating that the significant value was less than 0.05 as consideration. The effect size found through the calculation of Eta Squared proposed by Cohen was 0.08, categorized as a high level. Conclusion: It could be concluded that there was an effect of project-based learning assisted with flashcards towards students’ learning outcomes in learning Pencak Silat since this study is focused on learning.